Natural Transformation in Mesophilic and Thermophilic Bacteria: Identification and Characterization of Novel, Closely Related Competence Genes in Acinetobacter sp. Strain BD413 and Thermus thermophilus HB27 - Friedrich, Alexandra (American Society for Microbiology, 2001)
The mesophile Acinetobacter sp. strain BD413 and the extreme thermophile Thermus thermophilus HB27 display high frequencies of natural transformation. In this study we identified and characterized a novel competence gene in Acinetobacter sp. strain BD413, comA, whose product displays significant similarities to the competence proteins ComA and ComEC in Neisseria and Bacillus species. Transcription of comA correlated with growth phase-dependent transcriptional regulation of the recently identified pilin-like factors of the transformation machinery. This finding strongly suggests that comA is part of a competence regulon. Examination of the genome sequence of T. thermophilus HB27 led to detection of a comA/comEC-like open reading frame (ORF) which is flanked by an ORF whose product shows significant similarities to the Bacillus subtilis competence protein ComEA. To examine whether these two ORFs, designated comEC and comEA, are implicated in natural transformation of T. thermophilus HB27, both were disrupted by using a thermostable kanamycin resistance marker. Natural transformation in comEC mutants was reduced 1,000-fold, whereas in comEA mutants the natural transformation phenotype was completely eliminated. These results strongly suggest that both genes, comEC and comEA, are required for natural transformation in T. thermophilus HB27. Several transmembrane α-helices are predicted based on the amino acid sequences of ComA in Acinetobacter sp. strain BD413 and ComEC in T. thermophilus HB27, which suggests that ComA and ComEC are located in the inner membrane and function in DNA transport through the cytoplasmic membrane.